Solid electrolyte membrane material, preparation method, membrane and device
The existing film materials with high ion conductivity and low swelling are solved by introducing charged side chain groups and aromatic compound groups into solid electrolyte membrane materials and using triflate reaction and crosslinking agents. The problem of insufficient ion conduction performance of materials in electrolytic water and fuel cells.
Patent Information
- Application Number
- CN202411264840.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing anionic solid electrolyte membrane materials are insufficient in the fields of electrolysis, electrodialysis and fuel cells, and materials with low swelling and high ion conductivity are difficult to achieve.
Using a solid electrolyte membrane material with a specific structure, its main raw materials include charged side chain groups and aromatic compound groups. Through the use of trifluoromethanesulfonic acid reaction and crosslinking agent, polymers are prepared to form Membrane materials with high ion conductivity and low swelling.
It achieves high ion conduction and low swelling properties of membrane materials, and is suitable for electrochemical fields such as alkaline electrolytic water and fuel cells.
Smart Images

Figure CN119119429A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a solid electrolyte membrane material, a preparation method, a membrane and a device. Background Art
[0002] Anionic solid electrolyte membrane materials play an important role in the fields of water electrolysis, electrodialysis, flow batteries and fuel cell technology. Ion conduction is the most important function of solid electrolyte membrane materials. The ion transmission channel constructed by the existence of microcrystalline regions in the membrane material in the solid electrolyte is the core of the ion conduction function. The separation of hydrophilic and hydrophobic phases can effectively construct microcrystalline regions to promote ion conduction. Therefore, exploring new anionic solid electrolyte membrane materials so that solid electrolyte membrane materials can have high ion conduction performance, low swelling and high ion conductivity is of great significance for the development of anionic solid electrolyte membrane materials.
[0003] Therefore, in view of the above technical problems, it is necessary to provide a solid electrolyte membrane material, preparation method, membrane and device.
[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention
[0005] The object of the present invention is to provide a solid electrolyte membrane material, a preparation method, a membrane and a device.
[0006] It should be noted that: in the expression of the structural formula or structural simplified formula of the present invention, and Both refer to substitution sites or active sites.
[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:
[0008] Solid electrolyte membrane material, its main raw materials have the following structure:
[0009] Wherein, m and n are positive integers; Ar2 is an aromatic compound group; R7 is a side chain group with a charge; R8 is Wherein R1 is an alkyl group or an aryl group or a halogen-substituted alkyl group or a halogen-substituted aryl group, R2-R6 are independently selected from hydrogen, an alkyl group, an aryl group, a halogen group, an alkyl group substituted with a halogen group, and at least one of R2-R6 is fluorine; and in the main raw material, the molar ratio of R8 to Ar2 is 0.01-50% (i.e., m / (m+n) is 0.01-50%). Preferably, R1 is trifluoromethyl.
[0010] In one or more embodiments of the present invention, the charged side chain group is a side chain group having an ammonium salt.
[0011] In one or more embodiments of the present invention, the charged side chain group is selected from piperidinium or quinuclidine or quaternary ammonium salts.
[0012] In one or more embodiments of the present invention, the charged side chain groups are selected from:
[0013] Among them, R9, R 10 , R 11 , R 14 , R 15 , R 16 , R 19 R is independently selected from alkyl or aryl; 12 , R 17 R is independently selected from alkyl or halogen-substituted alkyl; 13 and R 18 are independently selected from alkyl or aryl; X is an anion. It only represents the symbol of the anion, not the valence state of the anion. 10 , R 11 , R 14 , R 15 , R 16 , R 19 Preferably, R 12 , R 17 Preferably, X is a halogen ion. When the anion is a carbonate, bicarbonate, hydroxide, sulfate, sulfonate, etc., it can be obtained by soaking and replacing with a corresponding solution.
[0014] in,
[0015] Can be correspondingly etc. as the main raw materials.
[0016] In one or more embodiments of the present invention, the anion is selected from halogen ion, carbonate, bicarbonate, hydroxide, trifluoromethanesulfonate, trifluorobenzenesulfonate anion, phosphorus hexafluoride anion, boron tetrafluoride anion, sulfate, sulfonate, nitrate.
[0017] In one or more embodiments of the present invention, the aromatic compound group is selected from phenyl, biphenyl, p-terphenyl, m-terphenyl, o-terphenyl, p-quadrenyl, m-quadrenyl, pentaphenyl, 1,2-diphenylethane, 3,3'-dimethylbiphenyl, triphenylphenyl, triptylenyl, fluorenyl and its derivative group with at least one alkyl substituent, carbazolyl and its N-alkyl carbazole derivative, anthracene, phenanthrenyl, naphthyl, and the above groups all provide two substitution positions. The derivative group of the alkyl substituent of the fluorenyl group can be selected from methylfluorenyl, dimethylfluorenyl and ethyl or more other alkyl substituted groups. The N-alkyl carbazole derivative can be selected from N-methyl carbazolyl, N-ethyl carbazolyl, etc. Preferably, the substitution position of the derivative group is at least position 9.
[0018] In one or more embodiments of the present invention, a cross-linking agent is further included, and the cross-linking agent includes a polyhalogenated hydrocarbon.
[0019] In one or more embodiments of the present invention, a method for preparing a solid electrolyte membrane material is characterized by comprising:
[0020] The raw material monomer is dissolved in the solution, and trifluoromethanesulfonic acid is slowly added under ice bath conditions to react to obtain a viscous solution;
[0021] Slowly add the viscous solution dropwise into water or alcohol solution to precipitate solid;
[0022] The solid is immersed in a potassium carbonate solution and stirred, washed and dried, and then a solvent and a salt-forming small molecule are added to react to obtain a reaction product. Preferably, the solvent is selected from DMSO or DMAc or NMP. Preferably, the alcohol solution is a mixture of alcohol and water in any ratio. The alcohol can be a monohydric alcohol or polyhydric alcohol with a C5 or lower content such as methanol and ethanol.
[0023] In one or more embodiments of the present invention, the electrolyte membrane is: a membrane formed by a first casting solution made of a solid electrolyte membrane material and / or an additive; or a membrane formed by combining a second casting solution made of a solid electrolyte membrane material and / or an additive with a support layer. The preferred support layer can be a porous support structure, such as a porous membrane or a mesh.
[0024] In one or more embodiments of the present invention, the device having ion conduction function includes an electrode, and the electrode includes an electrolyte membrane. The device is mainly used in electrochemical fields such as alkaline water electrolysis, fuel cells, electrodialysis devices, and electrochemical energy storage (such as liquid flow batteries, etc.).
[0025] Compared with the prior art, the solid electrolyte membrane material, preparation method, membrane and device of the present invention are simple to prepare and have high ion conductivity, while having low swelling and high ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 is the NMR graph of the polymer in Example 1 of the present invention;
[0028] Figure 2 is the NMR graph of the polymer in Example 16 of the present invention;
[0029] Figure 3 is a comparison chart of ionic conductivity and swelling ratio of the polymers in Examples 1 and 16 of the present invention;
[0030] Figure 4 is a tensile strain-stress comparison diagram of the polymers in Examples 1 and 16 of the present invention;
[0031] Figure 5 1 is a comparison chart of the ionic conductivity of the polymers in Examples 1 and 16 of the present invention. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0033] The preparation process comprises the following steps in sequence:
[0034] a) Synthesis of ion-conducting polymer compositions
[0035] One method is to dissolve aromatic compound monomer units, ketone-containing monomer units and aromatic fluorine-containing ketone structural units in a dichloromethane or trichloromethane solution. The molar ratio of aromatic monomer to ketone-containing monomer is 1:0.8 to 1:2, slowly add trifluoromethanesulfonic acid under ice bath conditions, wherein the equivalent of trifluoromethanesulfonic acid is 1-10 times the molar amount of aromatic compound, react at 0-80 degrees for 1-48 hours, obtain a viscous solution, slowly drip into ethanol or methanol or aqueous solution, and precipitate solid. Soak in 1M potassium carbonate and stir for 1-24 hours, filter, wash and dry, take 1g of solid, add 20ml of DMSO, add 0.5-10 times the molar amount of aromatic monomer molecular units for salt formation (including monohalogenated hydrocarbon compounds or polyhalogenated hydrocarbon compounds or amine compounds), and react at room temperature for 4 hours or more. Then add an appropriate amount of crosslinking agent, continue to react for more than 12 hours, drip the obtained solution into ethyl acetate to obtain a solid product, and dry at 60 degrees to obtain the final high molecular polymer. Dissolve 1 g of polymer in 20 ml of DMSO, DMAc or NMP solution to obtain the slurry required for film formation.
[0036] The second method can be: dissolving aromatic compound monomer units, ketone-containing monomer units and aromatic fluorine-containing ketone structural units in a dichloromethane or trichloromethane solution. The molar ratio of aromatic monomer to ketone-containing monomer is 1:0.8 to 1:2, slowly adding trifluoromethanesulfonic acid under ice bath conditions, wherein the equivalent of trifluoromethanesulfonic acid is 1-10 times the molar amount of aromatic compound, reacting at 0-80 degrees for 1-48 hours, obtaining a viscous solution, slowly dripping into ethanol or methanol or aqueous solution, and precipitating solid. Soaking in 1M potassium carbonate and stirring for 1-24 hours, filtering, washing, drying, taking 1g of solid, adding 20ml of DMSO, adding 0.5-10 times the molar amount of aromatic monomer equivalents of molecular units for salt formation (including monohalogenated hydrocarbon compounds or polyhalogenated hydrocarbon compounds or amine compounds small molecules), reacting at room temperature for more than 12 hours, dripping the obtained solution into ethyl acetate to obtain a solid product, and drying at 60 degrees to obtain the final high molecular polymer. Dissolve 1g polymer in 20ml DMSO or DMAc or NMP solution to obtain the slurry required for film formation. The third method can be: other additives can be added to the solutions of the above two schemes to form a slurry, that is, a casting solution. The additives here can be inorganic hydrophilic oxides, etc. The inorganic hydrophilic oxides are selected from one or more of zirconium oxide, titanium dioxide, barium sulfate, magnesium hydroxide, zinc carbonate, nickel hydroxide, and hydrotalcite materials, preferably zirconium oxide and barium sulfate. The particle size of the inorganic hydrophilic oxide is between 1nm-1μm, preferably 5nm-500nm. The inorganic hydrophilic oxide accounts for 0-60% of the mass fraction of the polymer, and the preferred range is 10-30%.
[0037] c) Preparation of anion exchange membrane
[0038] Anion exchange membranes are divided into three categories
[0039] (1) Directly cast the casting liquid onto a flat substrate. The material of the flat substrate can be PE, PET, PP, PTFE, glass, etc., among which PET is preferred. Dry at 80°C to form a film.
[0040] (2) Lay the porous support layer evenly on the glass substrate. The porous support layer is selected from polypropylene (PP), polyethylene (PE), polysulfone (PS), polyphenylene sulfide (PPS), polyamide / nylon (PA), polyethersulfone (PES), polyphenylene sulfone (PPS), polyethylene terephthalate (PET), polyetheretherketone (PEEK), sulfonated polyetheretherketone (s-PEEK), expanded polytetrafluoroethylene (E-PTFE), chlorotrifluoroethylene (CTFE), copolymers of ethylene and tetrafluoroethylene (ETFE) or chlorotrifluoroethylene (ECTFE), polyimide, polyetherimide and meta-aramid (m-aramide) to prepare fabrics and non-woven fabrics, preferably EPTFE. The thickness of the porous support layer is 1-60μm, preferably 2μm-40μm. The porosity of the porous support layer is 40-90%, preferably 50-80%. Use a Meyer rod to evenly coat the casting solution on the ePTFE, then put it into an 80°C oven for drying and then take it out.
[0041] (3) Mix the casting solution obtained above with an appropriate amount of additives such as inorganic hydrophilic oxides. Then the mixed casting solution can be directly cast onto a flat substrate, the material of which can be PE, PET, PP, PTFE, glass, etc., preferably PET, or coated onto a porous support layer by a Meyer rod. Dry at 80°C to form a film.
[0042] Including but not limited to the following embodiments, the ethanol solution can be directly replaced by any monohydric alcohol or polyhydric alcohol below C5 or any mixture of the aforementioned alcohol and water, or water, without affecting the implementation of the technical solution of the present application.
[0043] Example 1: (15%)
[0044] P-terphenyl, N-methylpiperidone, 1-(3,5-difluorophenyl)-2,2,2-trifluoroethyl ketone and dichloromethane were mixed, the amount of terphenyl was 2.3g, the amount of N-methylpiperidone was 0.96g, the amount of 1-(3,5-difluorophenyl)-2,2,2-trifluoroethyl ketone was 0.315g, and the amount of dichloromethane was 7ml. Trifluoromethanesulfonic acid was slowly added under ice bath conditions, wherein the amount of trifluoromethanesulfonic acid was 7ml. The reaction was carried out in an ice bath for 8h to obtain a viscous solution, which was slowly dripped into a 30v / v% ethanol solution to precipitate a solid. The solution was immersed in 1M potassium carbonate and stirred for 8 hours. After washing, filtering and drying, the product was obtained as follows.
[0045]
[0046] Take 1g of the above solid and add 20ml of DMSO, add 1.45g of iodomethane, and react at room temperature for 12h. The obtained solution is dripped into ethyl acetate to obtain a solid product, which is dried at 60 degrees to obtain the final polymer. Dissolve 1g of polymer in 20ml of DMSO solution to obtain the slurry required for film formation. Directly cast the casting solution onto glass. Dry at 80℃ to form a film.
[0047]
[0048] Products such as Figure 1 As shown, 6.77ppm is the hydrogen signal at position 1, 7.22-7.23ppm is the signal at position 2, 7.58-7.83ppm is the aromatic signal on the benzene ring in terphenyl, 3.38ppm is the hydrogen signal at position 4, but it slightly overlaps with the signal of the water peak in deuterated DMSO, 3.16ppm is the signal at position 3, 2.88ppm is the hydrogen signal at position 5, and 2.50ppm is the signal of deuterated DMSO.
[0049] Example 2: (25%)
[0050] The difference from Example 1 is that the amount of N-methylpiperidone is 0.84 g, the amount of 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is 0.525 g, and the amount of iodomethane is 1.27 g.
[0051] Example 3: (5%)
[0052] The difference from Example 1 is that the amount of N-methylpiperidone is 1.07 g, the amount of 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is 0.105 g, and the amount of iodomethane is 1.61 g.
[0053] Example 4: (1%)
[0054] The difference from Example 1 is that the amount of N-methylpiperidone is 1.11 g, the amount of 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is 0.021 g, and the amount of iodomethane is 1.69 g.
[0055] Example 5: (50%)
[0056] The difference from Example 1 is that the amount of N-methylpiperidone is 0.565 g, the amount of 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is 1.05 g, and the amount of iodomethane is 0.85 g.
[0057] Example 6: (0.1%)
[0058] The difference from Example 1 is that the amount of N-methylpiperidone is 1.13 g, the amount of 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is 0.0021 g, and the amount of iodomethane is 1.72 g.
[0059] Embodiment 7:
[0060] The difference from Example 1 is that 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is replaced by 2,2,2,4'-tetrafluoroacetophenone in an amount of 0.288 g.
[0061]
[0062] Embodiment 8:
[0063] The difference from Example 1 is that 1-(3,5-difluorophenyl)-2,2,2-trifluoroethanone is replaced by 2,2,2',3',4'-hexafluoroacetophenone, and the amount used is 0.342 g.
[0064]
[0065] Embodiment 9:
[0066] The difference from Example 1 is that 2,2,2,4'-tetrafluoroacetophenone is replaced by 2,2,2',3',4',5'-heptafluoroacetophenone, and the amount used is 0.369 g.
[0067]
[0068] Embodiment 10:
[0069] The difference from Example 1 is that 2,2,2,4'-tetrafluoroacetophenone is replaced by 2,2,2',3',4',5',6'-octafluoroacetophenone, the amount used is 0.369 g, and the ice bath reaction time is adjusted to 12 h.
[0070]
[0071] Embodiment 11:
[0072] The difference from Example 1 is that p-terphenyl is replaced by diphenyl, and the amount of diphenyl used is 1.54 g.
[0073]
[0074] Embodiment 12:
[0075] The difference from Example 1 is that p-terphenyl is replaced with 1.15 g m-terphenyl and 1.15 g p-terphenyl, and the ice bath reaction time is adjusted to 6 h.
[0076]
[0077] Example 13
[0078] The difference from Example 1 is that p-terphenyl is replaced by 1.15 g p-terphenyl and 0.97 g 9,9-dimethylfluorene, and the ice bath reaction time is adjusted to 12 h.
[0079]
[0080] Embodiment 14
[0081] The difference from Example 1 is that an expanded polytetrafluoroethylene membrane (E-PTFE) with a thickness of 10 μm is evenly spread on a glass substrate, the obtained slurry is poured on it, and dried at 80° C. for 12 hours to form a thin film substance with fillers in the pores of the expanded polytetrafluoroethylene membrane.
[0082] Embodiment 15
[0083] The difference from Example 1 is: 0.1 g of 30 μm zirconium oxide powder is added to the obtained slurry, stirred evenly to obtain a heterogeneous slurry, a 10 μm thick expanded polytetrafluoroethylene membrane (E-PTFE) is evenly spread on a glass substrate, the obtained heterogeneous slurry is poured on it, and dried at 80°C for 12 hours to form a film.
[0084] Example 16
[0085] The difference from Example 1 is that N-methylpiperidone is replaced by 3-quinuclidinone, the amount used is 1.482 g, and the ice bath reaction is adjusted to room temperature for 48 hours.
[0086]
[0087] Products such as Figure 2As shown, 7.22-7.55ppm are aromatic signals on the benzene ring in terphenyl, 6.77 and 7.22 signals are hydrogen signals at positions 1 and 2, 4.51ppm is the signal of hydrogen at position 5, 3.17-3.62ppm are signals at positions 6 and 7, which slightly overlap with the signal of the water peak in deuterated DMSO, 1.84 and 2.07ppm are hydrogen signals at position 4, and 2.50ppm is the signal of deuterated DMSO.
[0088] Embodiment 17
[0089] The difference from Example 1 is that N-methylpiperidone is replaced by 4-trifluoroacetylbenzyl bromide (CAS: 78126-14-4) in an amount of 1.482 g, and methyl iodide is replaced by trimethylamine hydrochloride in an amount of 1.91 g.
[0090]
[0091] Embodiment 18
[0092] The difference from Example 1 is that 0.215 g of 1,4-dibromobutane was added after methyl iodide was added and reacted for 4 hours.
[0093]
[0094] Comparative Example 1
[0095] Mix terphenyl and N-methyl-4-piperidone, the amount of terphenyl is 2.3g, the amount of N-methyl-4-piperidone is 1.13g, and the amount of dichloromethane is 7ml. Slowly add trifluoromethanesulfonic acid under ice bath conditions, where the amount of trifluoromethanesulfonic acid is 7ml, react in an ice bath for 8h to obtain a viscous solution, slowly drip it into an ethanol solution, and precipitate a solid. Soak it in 1M potassium carbonate and stir it for 8 hours. After filtering and drying, take 1g of the solid, add 20ml of DMSO, add 1ml of iodomethane, react at room temperature for 12h, and drip the obtained solution into ethyl acetate to obtain a solid product. Dry it at 60 degrees to obtain the final polymer. Dissolve 1g of polymer in 20ml of DMSO solution to obtain the slurry required for film formation. Cast the casting solution directly onto glass. Dry it at 80℃ to form a film.
[0096]
[0097] Comparative Example 2
[0098] Mix terphenyl and 3-quinuclidine ketone, the amount of terphenyl is 2.3g, the amount of 3-quinuclidine ketone is 1.24g, and the amount of dichloromethane is 7ml. Slowly add trifluoromethanesulfonic acid under ice bath conditions, where the amount of trifluoromethanesulfonic acid is 7ml, react at room temperature for 48h, obtain a viscous solution, slowly drip into an ethanol solution, and precipitate a solid. Soak in 1M potassium carbonate and stir for 8 hours. After filtering and drying, take 1g of the solid, add 20ml of DMSO, add 1ml of iodomethane, react at room temperature for 12h, and drip the obtained solution into ethyl acetate to obtain a solid product. Dry at 60 degrees to obtain the final polymer. Dissolve 1g of polymer in 20ml of DMSO solution to obtain the slurry required for film formation. Cast the casting solution directly onto glass. Dry at 80℃ to form a film.
[0099]
[0100] Electrochemical performance test
[0101] The hydroxyl ion conductivity test was performed using the Chenhua electrochemical workstation. The anion exchange membrane was soaked in 80-degree 1M KOH solution overnight for 12 hours, and then repeatedly washed with deionized water until the KOH solution on the surface was completely washed off. The hydroxyl ion conductivity test was then performed at different temperatures using the four-probe method. Figure 3 During the long-term test, the membrane was immersed in 80-degree 1M KOH solution for a long time, and then taken out for ion conductivity test after different time periods. Figure 5 shown.
[0102] The test method for swelling performance is as follows: Cut the prepared anion exchange membrane into square-sized (3cm×3cm) membrane samples, soak them in 80-degree 1M KOH solution for 12 hours, take out the membrane sample, quickly wipe off the residual liquid on the surface of the membrane sample with filter paper, and measure the thickness T1 of the membrane sample. After that, bake the membrane sample at 60°C for 0.5h, measure the thickness of the membrane sample in the dry film state, and record it as T2. The swelling rate of the anion exchange membrane is calculated as follows: Swelling rate = [(T1-T2) / T2]×100%. The test results are shown in the following table:
[0103] The mechanical properties test was performed by cutting the sample into a spindle-shaped membrane with a center width of 2 mm and a center length of 1.5 cm, and then testing it on an Instron universal mechanical tester, such as Figure 4 shown.
[0104] As shown in the following table, the swelling ratio and ionic conductivity of each embodiment and comparative example are shown:
[0105]
[0106]
[0107] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0108] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A solid electrolyte membrane material, the main raw material of which has the following structure: in, m and n are positive integers; Ar2 is an aromatic compound group; R7 is a side chain group with a charge; R8 is wherein R1 is an alkyl group or an aryl group or a halogen-substituted alkyl group or a halogen-substituted aryl group, R2-R6 are independently selected from hydrogen, an alkyl group, an aryl group, a halogen, a halogen-substituted alkyl group, a halogen-substituted aryl group, and at least one of R2-R6 is fluorine; And the molar ratio of R8 to Ar2 in the main raw material is 0.01-50%.
2. The solid electrolyte membrane material according to claim 1, characterized in that: The side chain group with charge is a side chain group with ammonium salt.
3. The solid electrolyte membrane material according to claim 2, characterized in that: The charged side chain group is selected from piperidinium or quinuclidine or quaternary ammonium salts.
4. The solid electrolyte membrane material according to claim 3, characterized in that: The charged side chain groups are selected from: Among them, R9, R 10 , R 11 , R 14 , R 15 , R 16 , R 19 R is independently selected from alkyl or aryl; 12 , R 17 R is independently selected from alkyl or halogen-substituted alkyl; 13 and R 18 are independently selected from alkyl or aryl; X is an anion.
5. The solid electrolyte membrane material according to claim 4, characterized in that: The anion is selected from the group consisting of halogen ion, carbonate, bicarbonate, hydroxide, trifluoromethanesulfonate, p-trifluorobenzenesulfonic acid anion, phosphorus hexafluoride anion, boron tetrafluoride anion, sulfate, sulfonate, and nitrate.
6. The solid electrolyte membrane material according to claim 1, characterized in that: The aromatic compound group is selected from phenyl, biphenyl, p-terphenyl, m-terphenyl, o-terphenyl, p-quaterphenyl, m-quaterphenyl, pentyl, 1,2-diphenylethane, 3,3'-dimethylbiphenyl, triphenylphenyl, triptylenyl, fluorenyl and its derivative groups having at least one alkyl substituent, carbazole and its N-alkyl carbazole derivative groups, anthracene, phenanthrenyl, naphthyl, and the above groups all provide two substitution positions.
7. The solid electrolyte membrane material according to any one of claims 1 to 6, characterized in that: Also included is a cross-linking agent comprising a polyhalogenated hydrocarbon.
8. The method for preparing a solid electrolyte membrane material according to any one of claims 1 to 7, characterized in that: include: The raw material monomer is dissolved in the solution, and trifluoromethanesulfonic acid is slowly added under ice bath conditions to react to obtain a viscous solution; Slowly add the viscous solution to water or alcohol solution to precipitate solid; The solid is immersed in a potassium carbonate solution and stirred, and after washing and drying, a solvent and a salt-forming small molecule are added to react to obtain a reaction product.
9. An electrolyte membrane, comprising: a membrane formed by a first casting liquid made from the solid electrolyte membrane material and / or additives described in any one of claims 1 to 7; or a membrane formed by combining a second casting liquid made from the solid electrolyte membrane material and / or additives described in any one of claims 1 to 7 with a supporting layer. 10 . A device having an ion-conducting function, comprising an electrode, wherein the electrode comprises the electrolyte membrane according to claim 9 .
Citation Information
Patent Citations
Ionomer containing alkaline hydrolysis-resistant cationic group and fluorocarbon side chain as well as preparation method and application of ionomer
CN112552488A
Polyelectrolyte material and preparation method thereof and polyelectrolyte membrane
CN113621131A
Preparation method and application of cross-linked anion exchange membrane
CN115548397A
Perfluoro side chain grafted anion exchange membrane and preparation method thereof
CN116845307A
Ultralow-swelling anti-free-radical polyaryl anion exchange membrane and preparation method thereof
CN117024924A
